Toughened polyamide material with high melt strength as well as preparation method and application thereof

Micro-crosslinked toughened polyamide masterbatches are prepared through pre-crosslinking and reaction grafting technology, and combined with aliphatic polyamide to form a mutual transfer network structure, solving the problems of low melt strength and poor creep resistance of polyamide pipes, and achieving high melt strength and toughness material preparation, suitable for the production of larger diameter pipes.

CN119798978APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510000873.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the preparation process, existing polyamide pipes have low melt strength and are easy to fuse and sag, making it difficult to prepare larger diameter pipes, and have poor creep resistance.

Method used

Micro-crosslinked toughened polyamide masterbatches are prepared by pre-crosslinking and reaction grafting technology, and combined with aliphatic polyamides to form a mutually transfer network structure to improve melt strength and toughness.

Benefits of technology

It significantly improves the melt strength and toughness of polyamide materials, improves the melt sag phenomenon during processing, can prepare larger diameter pipes, and improves creep resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225056440000071
    Figure BDA0005225056440000071
  • Figure BDA0005225056440000101
    Figure BDA0005225056440000101
  • Figure BDA0005225056440000102
    Figure BDA0005225056440000102
Patent Text Reader

Abstract

The invention relates to a toughened polyamide material with high melt strength as well as a preparation method and application thereof. The toughened polyamide material with high melt strength comprises aliphatic polyamide, micro-crosslinking toughened polyamide master batch, a plasticizer, an antioxidant, an anti-ultraviolet agent and a lubricant. According to the high-melt-strength toughened polyamide material, the dispersity of a toughening agent is improved, the compatibility between the toughening agent and polyamide is improved, the toughness and creep resistance are further improved, and the high-melt-strength toughened polyamide material can be applied to the fields of gas pipes, hydrogen conveying pipes, oil conveying pipes, industrial pipes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pipes and preparation thereof, and particularly relates to a toughened polyamide material with high melt strength and a preparation method and application thereof. Background Art

[0002] With the rapid development of polymer material science and technology, the deepening of the development and utilization of plastic pipes, and the continuous improvement of production processes, plastic pipes are fully demonstrating their excellent performance. Today, plastic pipes are no longer mistaken as "cheap substitutes" for metal pipes. Replacing steel with plastic and developing pipeline transportation are the development trends of the world's materials and transportation industries. Pipeline transportation has significant social and economic benefits and has always been the preferred means of transportation in the transportation industry of industrially developed countries.

[0003] Polyamide is an important engineering plastic, and its output ranks first among the five major general-purpose engineering plastics. Its main characteristics are: (1) good wear resistance and self-lubricating properties; (2) chemical properties: due to high cohesive energy and crystallinity, it has excellent chemical resistance and can only be dissolved by highly polar solvents such as phenol, cresol, and formic acid; (3) mechanical properties: high tensile strength of (50-80) MPa, flexural strength of (80-120) MPa, and impact strength (notched simple beam) of (4-20) kJ / m 2 At the same time, polyamide also has some disadvantages: (1) low molecular weight, low melt strength during pipe preparation, easy to sag, and difficult to prepare large diameter pipes; (2) poor creep resistance, prone to damage during long-term use. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a toughened polyamide material with high melt strength. First, a micro-crosslinked toughened polyamide masterbatch is prepared by pre-crosslinking and reaction grafting. After adding polyamide, an interconductive network structure can be formed, the melt strength can be improved, and the sag can be improved, so that larger diameter pipes can be prepared; at the same time, the dispersibility of the toughening agent is improved, and the compatibility between the toughening agent and polyamide is increased, thereby improving the toughness and creep resistance. It can be used in the fields of gas pipes, hydrogen pipes, oil pipes, industrial pipes, etc.

[0005] Another object of the present invention is to provide a method for preparing the toughened polyamide material with high melt strength.

[0006] Another object of the present invention is to provide applications of the toughened polyamide material with high melt strength.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] A toughened polyamide material with high melt strength, comprising the following components in percentage by weight:

[0009] Aliphatic polyamide 59-91wt%, preferably 71-84wt%;

[0010] Micro-crosslinked toughened polyamide masterbatch 5-30wt%, preferably 10-20wt%;

[0011] Plasticizer 3-10wt%, preferably 5-8wt%;

[0012] Antioxidant 0.05-1.0wt%, preferably 0.1-0.5wt%;

[0013] Anti-ultraviolet agent 0.05-1.0wt%, preferably 0.1-0.5wt%;

[0014] Lubricant 0.05-0.5wt%, preferably 0.1-0.3wt%;

[0015] In some specific embodiments, the aliphatic polyamide is selected from one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12, preferably one or more of PA1012, PA1212, PA11, and PA12, and most preferably, the polyamide is PA12.

[0016] In some specific embodiments, the antioxidant is selected from one or more of 1010, 1076, 1098, 168, 1330, 1135, and 245, preferably 1076 and 168.

[0017] In some specific embodiments, the plasticizer is selected from at least one of N-butylbenzenesulfonamide, N,N-diallylbenzenesulfonamide, N,N-diallyl-4-methylbenzenesulfonamide, 4-methyl-N,N-di(prop-2-ynyl)benzenesulfonamide, and N-ethynyl-N,4-dimethylbenzenesulfonamide, preferably N-butylbenzenesulfonamide.

[0018] In some specific embodiments, the anti-ultraviolet agent is selected from UV-531, UV-327, UV-328, UV-329, UV-326, UV-312, and UV-234, preferably UV-312.

[0019] In some specific embodiments, the lubricant is selected from one or more of titanate, stearic acid, erucamide, oleamide and silicone.

[0020] In some specific embodiments, the method for preparing the micro-crosslinked toughened polyamide masterbatch comprises:

[0021] (1) Preparation of cross-linked polyamide

[0022] Add polyamide and crosslinking agent into the reactor, use nitrogen to purge and replace, raise the temperature and stir the reaction after nitrogen replacement is completed; then remove small molecules and by-products by vacuum, pressurize with nitrogen again after no small molecules are removed, discharge the materials from the bottom of the reactor and pelletize them through water to obtain crosslinked polyamide;

[0023] (2) Preparation of micro-crosslinked toughened polyamide masterbatch

[0024] The cross-linked polyamide, toughening agent, compatibilizer and initiator are fully and uniformly mixed according to proportion, and the mixture is extruded by a twin-screw extruder, stretched, watered and pelletized to obtain a slightly cross-linked toughened polyamide masterbatch.

[0025] In some specific embodiments, the polyamide in step (1) is one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12, preferably one or more of PA1012, PA1212, PA11, and PA12, and most preferably, the polyamide is PA12.

[0026] In some specific embodiments, the cross-linking agent in step (1) is one or a mixture of two of TMPTMA, TMPTA, and TAIC;

[0027] Preferably, the weight ratio of the polyamide to the cross-linking agent is 90-99wt%:1-10wt%, preferably 92-95wt%:5-8wt%.

[0028] In some specific embodiments, in step (1), after nitrogen replacement is completed, the temperature of the stirring reaction is increased to 190-250° C. and the time is 5-10 hours;

[0029] Preferably, the nitrogen pressurization temperature is 210-280° C. and the pressure is 0.2-0.6 MPa.

[0030] In some specific embodiments, the toughening agent in step (2) is one or more of EPDM rubber, styrene-butadiene-styrene terpolymer, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene copolymer, polyolefin elastomer, and nylon elastomer; preferably, the toughening agent is one or more of EPDM rubber, styrene-butadiene-styrene terpolymer, and polyolefin elastomer.

[0031] In some specific embodiments, the compatibilizer is maleic anhydride.

[0032] In some specific embodiments, the initiator is one or more of dicumyl peroxide, benzoyl peroxide, and tert-butyl peroxide, preferably dicumyl peroxide.

[0033] In some specific embodiments, the weight ratio of the cross-linked polyamide: toughening agent: compatibilizer: initiator is 10-89wt%: 10-89wt%: 0.1-5wt%: 0.1-0.5wt%, preferably 39-59wt%: 39-59wt%: 1-4wt%: 0.15-0.3wt%.

[0034] In some specific embodiments, the processing temperature of the twin-screw extruder in step (2) is 240-280° C., and the screw speed is 300-600 rpm.

[0035] On the other hand, the method for preparing the aforementioned high melt strength toughened polyamide material comprises the following steps:

[0036] Aliphatic polyamide, slightly cross-linked toughened polyamide masterbatch, plasticizer, antioxidant, anti-ultraviolet agent and lubricant are added to a mixer in proportion and mixed, and the mixed raw materials are added to a twin-screw feeding bin. The toughened polyamide material with high melt strength is obtained through twin-screw melt extrusion, drawing, water passing and pelletizing.

[0037] In some specific embodiments, the processing temperature of the twin-screw extruder is 240-280° C., and the screw speed is 300-600 rpm.

[0038] On the other hand, the aforementioned high melt strength toughened polyamide material or the high melt strength toughened polyamide material prepared by the aforementioned preparation method is used in the fields of gas pipes, hydrogen pipes, oil pipes, and industrial pipes.

[0039] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0040] (1) The cross-linked polyamide prepared by the present invention can ensure that the masterbatch has a high degree of cross-linking by adjusting the composition and addition amount of the cross-linking agent, adjusting the reaction temperature, reaction time and other processes; and shorten the reaction time and reduce the residual amount of small molecular substances by vacuuming, pressurizing and other methods.

[0041] (2) The micro-crosslinked toughened polyamide masterbatch prepared by the present invention can improve the dispersibility of the toughening agent and increase the compatibility between the toughening agent and polyamide through reactive grafting extrusion; the micro-crosslinked toughened polyamide masterbatch has good compatibility with polyamide and can easily form an interpenetrating network structure during melt blending, thereby increasing the melt strength of the polyamide material and improving the sag generated during the processing of the polyamide material.

[0042] (3) The present invention further improves the dispersibility of the toughening agent through secondary melt extrusion; the preparation method is simple, efficient and reliable; the prepared toughened polyamide material has high melt strength and can produce larger diameter pipes; it has excellent toughness and creep resistance; it can be industrialized and mass-produced using existing equipment; and it can be applied to gas pipes, hydrogen pipes, oil pipes, industrial pipes and other fields. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0044] The present invention provides a toughened polyamide material with high melt strength, and the preparation steps thereof include:

[0045] (1) Preparation of cross-linked polyamide

[0046] Polyamide and a cross-linking agent are added to a reactor, and nitrogen is used for purging and replacement. After the nitrogen replacement is completed, the temperature is increased and stirred to react for a period of time; after a period of reaction, small molecules and by-products are removed by vacuum, and after no small molecules are removed, nitrogen is pressurized at a certain temperature, and the material is discharged from the bottom of the reactor and pelletized through water to obtain cross-linked polyamide.

[0047] (2) Preparation of micro-crosslinked toughened polyamide masterbatch

[0048] The cross-linked polyamide, toughening agent, compatibilizer and initiator are fully and uniformly mixed in a certain proportion, and the mixture is extruded by a twin-screw extruder, stretched, watered and pelletized to obtain a slightly cross-linked toughened polyamide masterbatch.

[0049] (3) Preparation of toughened polyamide materials with high melt strength

[0050] Aliphatic polyamide, slightly cross-linked toughened polyamide masterbatch, plasticizer, antioxidant, anti-ultraviolet agent, lubricant, etc. are added to a mixer in a certain proportion and mixed. The mixed raw materials are added to a twin-screw feeding bin, and the toughened polyamide material with high melt strength is obtained through twin-screw melt extrusion, drawing, water passing, and pelletizing.

[0051] In the method of the present invention, the polyamide in step (1) is one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12, preferably one or more of PA1012, PA1212, PA11, and PA12, and most preferably, the polyamide is PA12.

[0052] In the method of the present invention, the cross-linking agent is one of TMPTMA, TMPTA, and TAIC, or a mixture of two of them.

[0053] In the method of the present invention, the weight ratio of polyamide: cross-linking agent is 90-99wt%:1-10wt%, such as 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, etc., preferably 92-95wt%:5-8wt%.

[0054] In the method of the present invention, the temperature for the reaction in the nitrogen atmosphere in step (1) is 190-250°C, such as 200°C, 210°C, 220°C, 230°C, 240°C, etc., and the time is 5-10h, such as 6h, 7h, 8h, 9h, etc.

[0055] In the method of the present invention, the temperature of the nitrogen pressurization is 210-280°C, for example, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, etc., and the pressure is 0.2-0.6MPa, for example, 0.3MPa, 0.4MPa, 0.5MPa, etc.

[0056] In the method of the present invention, the toughening agent in step (2) is one or more of ethylene propylene diene monomer rubber, styrene-butadiene-styrene terpolymer, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene copolymer, polyolefin elastomer, and nylon elastomer; preferably, the toughening agent is one or more of ethylene propylene diene monomer rubber, styrene-butadiene-styrene terpolymer, and polyolefin elastomer.

[0057] In the method of the present invention, the compatibilizer is maleic anhydride.

[0058] In the method of the present invention, the initiator is one or more of dicumyl peroxide, benzoyl peroxide, and tert-butyl peroxide hexane, preferably dicumyl peroxide.

[0059] In the method of the present invention, the weight ratio of the cross-linked polyamide: toughening agent: compatibilizer: initiator is 10-89wt%: 10-89wt%: 0.1-5wt%: 0.1-0.5wt%, preferably 39-59wt%: 39-59wt%: 1-4wt%: 0.15-0.3wt%.

[0060] In the method of the present invention, the processing temperature of the twin-screw extruder in step (2) is 240-280°C, for example, 250°C, 260°C, 270°C, etc., and the screw speed is 300-600rpm, for example, 400rpm, 450rpm, 500rpm, 550rpm, etc.

[0061] In the method of the present invention, the aliphatic polyamide in step (3) is one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12, preferably one or more of PA1012, PA1212, PA11, and PA12, and most preferably, the polyamide is PA12.

[0062] In the method of the present invention, the antioxidant is one or more of 1010, 1076, 1098, 168, 1330, 1135, and 245, preferably 1076 and 168.

[0063] In the method of the present invention, the plasticizer is at least one of N-butylbenzenesulfonamide, N,N-diallylbenzenesulfonamide, N,N-diallyl-4-methylbenzenesulfonamide, 4-methyl-N,N-di(prop-2-ynyl)benzenesulfonamide, and N-ethynyl-N,4-dimethylbenzenesulfonamide, preferably N-butylbenzenesulfonamide.

[0064] In the method of the present invention, the anti-ultraviolet agent is UV-531, UV-327, UV-328, UV-329, UV-326, UV-312, UV-234, preferably UV-312.

[0065] In the method of the present invention, the lubricant is one or more of titanate, stearic acid, erucamide, oleamide and silicone.

[0066] In the method of the present invention, based on the total mass of each component, the weight percentage of each component in step (3) is as follows:

[0067] Aliphatic polyamide 59-91wt%, such as 60, 65, 70, 75, 80, 85, 90wt%, etc., preferably 71-84wt%;

[0068] 5-30wt% of slightly cross-linked toughened polyamide masterbatch, for example, 10, 15, 20, 25wt%, etc., preferably 10-20wt%;

[0069] Plasticizer 3-10wt%, such as 4, 5, 6, 7, 8, 9wt%, etc., preferably 5-8wt%;

[0070] Antioxidant 0.05-1.0wt%, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9wt%, etc., preferably 0.1-0.5wt%;

[0071] Anti-ultraviolet agent 0.05-1.0wt%, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9wt%, etc., preferably 0.1-0.5wt%;

[0072] Lubricant 0.05-0.5wt%, such as 0.06, 0.1, 0.2, 0.3, 0.4, 0.5wt%, etc., preferably 0.1-0.3wt%.

[0073] In the method of the present invention, the processing temperature of the twin-screw extruder in step (3) is 240-280°C, such as 250°C, 260°C, 270°C, etc., and the screw speed is 300-600rpm, such as 400rpm, 500rpm, etc.

[0074] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0075] The main sources of raw materials used in the examples of the present invention are as follows; other raw materials are common commercially available raw materials unless otherwise specified.

[0076] Table 1 Raw material information

[0077]

[0078]

Evaluation method

[0079] 1) Melt strength

[0080] According to ISO 16790 standard, the test was carried out on the German Gottfert-Rheotens71.97 equipment, with an extrusion temperature of 230°C and a pulling acceleration of 20 mm / S 2 When the polymer melt is extruded downward from the extruder die, it is pulled by two rollers mounted on a balance beam and moving in opposite directions until the melt strand breaks.

[0081] 2) Creep resistance

[0082] According to GB / T 32682-2016 standard, the test was carried out on the IPT full-notch creep tester-1598 equipment. The sample was prepared into a 100×10×10mm spline with a spline notch depth of 1.6mm, a tensile stress of 4.5MPa, and an ambient reagent temperature of 95°C. The spline was fixed with a special tool and immersed in the environmental reagent, and stretched at a constant tensile stress until the spline broke.

[0083] 3) Long-term pressure resistance of pipes

[0084] According to ISO 16486-2 standard, the test was carried out on the IPT hydrostatic tester-1720 equipment. The sample was made into a DN32 and 3mm thick pipe using a pipe extruder. The water temperature was 80℃ and the hoop stress was 11.5MPa. The pipe was sealed with a special fixture and immersed in high-temperature water, and a constant pressure was applied to it until the pipe was damaged.

[0085] Preparation Example 1

[0086] 2700g PA12 and 300g crosslinking agent were added to the reactor, and nitrogen was used for purging and replacement. After nitrogen replacement, the temperature was raised to 230°C and stirred for reaction for 5h. After the reaction was completed, small molecular substances and by-products were removed by vacuum, and then nitrogen was pressurized at 270°C with 0.5MPa, and the material was discharged from the bottom of the reactor and pelletized by water to obtain crosslinked PA12. 1200g crosslinked PA12, 2776g POE, 200g maleic anhydride, and 20g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered, and pelletized to obtain micro-crosslinked toughened polyamide masterbatch A.

[0087] Preparation Example 2

[0088] 2790g PA12 and 210g crosslinking agent were added to the reactor, and nitrogen was used for purging and replacement. After nitrogen replacement, the temperature was raised to 210°C and stirred for reaction for 7h. After the reaction, small molecular substances and by-products were removed by vacuum, and then nitrogen was pressurized at 250°C with 0.4MPa, and the material was discharged from the bottom of the reactor and pelletized through water to obtain crosslinked PA12. 1800g crosslinked PA12, 2112g POE, 160g maleic anhydride, and 12g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered, and pelletized to obtain micro-crosslinked toughened polyamide masterbatch B.

[0089] Preparation Example 3

[0090] 2850g PA12 and 150g crosslinking agent were added to the reactor, and nitrogen was used for purging and replacement. After nitrogen replacement, the temperature was raised to 210°C and stirred for reaction for 8.5h. After the reaction was completed, small molecular substances and by-products were removed by vacuum, and then nitrogen was pressurized at 230°C with 0.3MPa, and the material was discharged from the bottom of the reactor and pelletized through water to obtain crosslinked PA12. 2200g crosslinked PA12, 1628g POE, 80g maleic anhydride, and 8g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered, and pelletized to obtain a slightly crosslinked toughened polyamide masterbatch C.

[0091] Preparation Example 4

[0092] 2910g PA12 and 90g crosslinking agent were added to the reactor, and nitrogen was used for purging and replacement. After nitrogen replacement, the temperature was raised to 190°C and stirred for reaction for 9h. After the reaction was completed, small molecular substances and by-products were removed by vacuum, and then nitrogen was pressurized at 210°C with 0.2MPa, and the material was discharged from the bottom of the reactor and pelletized through water to obtain crosslinked PA12. 2800g crosslinked PA12, 980g POE, 20g maleic anhydride, and 4g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered, and pelletized to obtain a slightly crosslinked toughened polyamide masterbatch D.

[0093] Preparation Example 5

[0094] 2850g PA12 and 150g crosslinking agent were added to the reactor, and nitrogen was used for purging and replacement. After nitrogen replacement, the temperature was raised to 210°C and stirred for reaction for 8.5h. After the reaction was completed, small molecular substances and by-products were removed by vacuum, and then nitrogen was pressurized at 0.3MPa at 230°C, and the material was discharged from the bottom of the reactor and pelletized through water to obtain crosslinked PA12. 2200g crosslinked PA12, 1628g EPDM, 80g maleic anhydride, and 8g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered, and pelletized to obtain micro-crosslinked toughened polyamide masterbatch E.

[0095] Preparation Comparative Example 1

[0096] 2790g PA1010 and 210g crosslinking agent were added to the reactor, and nitrogen was used for purging and replacement. After nitrogen replacement, the temperature was raised to 220°C and stirred for reaction for 6h. After the reaction was completed, small molecular substances and by-products were removed by vacuum, and then nitrogen was pressurized at 240°C with 0.4MPa, and the material was discharged from the bottom of the reactor and pelletized through water to obtain crosslinked PA1010. 1800g crosslinked PA1010, 2112g POE, 160g maleic anhydride, and 12g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered, and pelletized to obtain a slightly crosslinked toughened polyamide masterbatch F.

[0097] Preparation Comparative Example 2

[0098] 1800g PA12, 2112g POE, 160g maleic anhydride and 12g DCP were fully mixed, extruded by a twin-screw extruder, stretched, watered and pelletized to obtain slightly cross-linked toughened polyamide masterbatch G.

[0099] Example Preparation of toughened polyamide material with high melt strength

[0100] Aliphatic polyamide, slightly cross-linked toughened polyamide masterbatch, plasticizer, antioxidant, anti-ultraviolet agent, lubricant, etc. are weighed in a certain mass ratio (see Table 2 for the specific ratio) and added to a mixer for mixing. The mixed raw materials are added to a twin-screw feeding bin, and the extrusion temperature is set to 260°C and the screw speed is set to 400rpm. The toughened polyamide material with high melt strength is obtained by melt extrusion, drawing, water passing, and pelletizing in a twin-screw extruder.

[0101] Table 2 Polyamide material component ratio (wt%)

[0102]

[0103] The polyamide composition embodiments and comparative examples were tested and verified by the above test method, and the specific performance is shown in Table 3.

[0104] Table 3 Performance of Examples and Comparative Examples

[0105]

[0106]

[0107] It can be seen from the results in Table 3 that the high melt strength toughened polyamide material created by the present invention has excellent performance, greatly improves the melt strength of the material, and has excellent creep resistance and long-term pressure resistance, and can be used to prepare larger caliber polyamide pipes.

[0108] By comparing Example 3 with Comparative Examples 2 and 3, it is found that the high melt strength toughened polyamide material of the present invention has significantly improved melt strength, creep resistance and long-term pressure resistance compared to the polyamide material using non-pre-crosslinked toughening masterbatch and the directly blended polyamide material, indicating that the high melt strength toughened polyamide material of the present invention can form a cross-linked interconducting network internally, improve the dispersibility of the toughening agent, increase the compatibility between the toughening agent and the polyamide, and thus improve the sag phenomenon during the processing of the polyamide material, greatly broadening the application field of the material.

[0109] By comparing Example 3, Example 6, and Example 7 with Comparative Example 1, preferred materials and proportions are selected in the preparation stage of toughened polyamide materials with high melt strength. Compared with other materials and proportions, PA12 has better performance, the masterbatch of the same material is more compatible with the substrate, and the performance of the obtained material is better.

[0110] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A toughened polyamide material with high melt strength, characterized in that: The composition comprises the following weight percentages: Aliphatic polyamide 59-91wt%, preferably 71-84wt%; Micro-crosslinked toughened polyamide masterbatch 5-30wt%, preferably 10-20wt%; Plasticizer 3-10wt%, preferably 5-8wt%; Antioxidant 0.05-1.0wt%, preferably 0.1-0.5wt%; Anti-ultraviolet agent 0.05-1.0wt%, preferably 0.1-0.5wt%; Lubricant 0.05-0.5wt%, preferably 0.1-0.3wt%.

2. The toughened polyamide material with high melt strength according to claim 1, characterized in that: The aliphatic polyamide is selected from one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12, preferably one or more of PA1012, PA1212, PA11, and PA12, and most preferably, the polyamide is PA12; and / or The antioxidant is selected from one or more of 1010, 1076, 1098, 168, 1330, 1135, 245, preferably 1076 and 168; and / or The plasticizer is selected from at least one of N-butylbenzenesulfonamide, N,N-diallylbenzenesulfonamide, N,N-diallyl-4-methylbenzenesulfonamide, 4-methyl-N,N-di(prop-2-ynyl)benzenesulfonamide, and N-ethynyl-N,4-dimethylbenzenesulfonamide, preferably N-butylbenzenesulfonamide; and / or The anti-ultraviolet agent is selected from UV-531, UV-327, UV-328, UV-329, UV-326, UV-312, UV-234, preferably UV-312; and / or The lubricant is selected from one or more of titanate, stearic acid, erucamide, oleamide and silicone.

3. The toughened polyamide material with high melt strength according to claim 1 or 2, characterized in that: The preparation method of the micro-crosslinked toughened polyamide masterbatch comprises: (1) Preparation of cross-linked polyamide Add polyamide and crosslinking agent into the reactor, use nitrogen to purge and replace, raise the temperature and stir the reaction after nitrogen replacement is completed; then remove small molecules and by-products by vacuum, pressurize with nitrogen again after no small molecules are removed, discharge the materials from the bottom of the reactor and pelletize them through water to obtain crosslinked polyamide; (2) Preparation of micro-crosslinked toughened polyamide masterbatch The cross-linked polyamide, toughening agent, compatibilizer and initiator are fully and uniformly mixed according to proportion, and the mixture is extruded by a twin-screw extruder, stretched, watered and pelletized to obtain a slightly cross-linked toughened polyamide masterbatch.

4. The toughened polyamide material with high melt strength according to claim 3, characterized in that: The polyamide in step (1) is one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12, preferably one or more of PA1012, PA1212, PA11, and PA12, and most preferably, the polyamide is PA12; and / or The cross-linking agent is one or a mixture of two of TMPTMA, TMPTA, and TAIC; Preferably, the weight ratio of the polyamide to the cross-linking agent is 90-99wt%:1-10wt%, preferably 92-95wt%:5-8wt%.

5. The toughened polyamide material with high melt strength according to claim 3, characterized in that: Step (1) after nitrogen replacement is completed, the temperature is raised to 190-250° C. and the stirring reaction time is 5-10 hours; Preferably, the nitrogen pressurization temperature is 210-280° C. and the pressure is 0.2-0.6 MPa.

6. The toughened polyamide material with high melt strength according to claim 3, characterized in that: The toughening agent in step (2) is one or more of EPDM rubber, styrene-butadiene-styrene terpolymer, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene copolymer, polyolefin elastomer, and nylon elastomer; preferably, the toughening agent is one or more of EPDM rubber, styrene-butadiene-styrene terpolymer, and polyolefin elastomer; and / or The compatibilizer is maleic anhydride; and / or The initiator is one or more of dicumyl peroxide, benzoyl peroxide, and tert-butyl peroxide, preferably dicumyl peroxide; Preferably, the weight ratio of the cross-linked polyamide: toughening agent: compatibilizer: initiator is 10-89wt%: 10-89wt%: 0.1-5wt%: 0.1-0.5wt%, preferably 39-59wt%: 39-59wt%: 1-4wt%: 0.15-0.3wt%.

7. The toughened polyamide material with high melt strength according to claim 6, characterized in that: The processing temperature of the twin-screw extruder in step (2) is 240-280° C., and the screw speed is 300-600 rpm.

8. The method for preparing a toughened polyamide material with high melt strength according to any one of claims 1 to 7, characterized in that: The following steps are involved: Aliphatic polyamide, slightly cross-linked toughened polyamide masterbatch, plasticizer, antioxidant, anti-ultraviolet agent and lubricant are added to a mixer in proportion and mixed, and the mixed raw materials are added to a twin-screw feeding bin. The toughened polyamide material with high melt strength is obtained through twin-screw melt extrusion, drawing, water passing and pelletizing.

9. The preparation method according to claim 8, characterized in that: The processing temperature of the twin-screw extruder is 240-280°C and the screw speed is 300-600rpm.

10. Use of the high melt strength toughened polyamide material according to any one of claims 1 to 7 or the high melt strength toughened polyamide material prepared by the preparation method according to any one of claims 8 to 9 in the fields of gas pipes, hydrogen pipes, oil pipes and industrial pipes.

Citation Information

Patent Citations

  • Toughened antistatic dual-functional plastic master batch for direct injection molding and preparation method thereof

    CN109370022A

  • Polyamide composition and preparation method thereof

    CN109749433A

  • Preparation method of flame-retardant-free low-flammability polyamide material

    CN114196200A

  • Toughened polyamide compositions having improved properties

    EP0375390A1